The Relationship Between Harmonious Familiy With Loneliness - Ratu Raisha Ihza Taftazana; Raudah Zaimah Dalimunthe; Rahmawati (Department of Guidance and Counseling, FIP, Undiksha, 2022)
The purpose of this study was to know the relationship between harmonious family with loneliness in 10th Grade 1 High School Pandeglang. Research conducted using quantitative methods with correlational types. The population in this study were students of 10th Grade 1 High School Pandeglang with a sample of 218 students studied. The sampling technique using probability sampling include simple random sampling. The instrument used to measure harmonious family and loneliness was a questionnaire created by the researcher. By the result of data analysis using statistical method with Product Moment analysis showed that the value of r-count < r-table was 0,01< 0,05 then the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted at a significance level of 5% so that it can be interpreted that there is a relationship between harmonious family with loneliness of the 10th Grade 1 High School Pandeglang in Academic Year of 2022/2023.